Mechanics of Biological Systems and Materials, Volume 6 Proceedings of the 2016 Annual Conference on Experimental and Applied Mechanics - Korach, Chad S.; Tekalur, Srinivasan Arjun; Zavattieri, Pablo (Conference Proceedings of the Society for Experimental Mechanics Series, 2017)
Mechanics of Biological Systems and Materials, Volume 6 of the Proceedings of the 2016 SEM Annual Conference & Exposition on Experimental and Applied Mechanics, the sixth volume of ten from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on a wide range of areas, including: Soft Material Mechanics Bio-Engineering and Biomechanics Cells Mechanics Biomaterials and Mechanics Across Multiple Scales Biomechanics Biotechnologies Traumatic Brain Injury Mechanics.